Resonant ultrasound spectroscopy of transition metal tetrachalcogenides (2023)
During this master's thesis, the set-up of resonant ultrasound spectroscopy (RUS) technique was developed at the Universidad de los Andes and a temperature-dependent experiment was carried out.